Filsafat Dasar dalam Konseling Psikoanalisis : Studi Literatur - Habsy, Bakhrudin All; Mufidha, Nazwatul; Shelomita, Cahyaning; Rahayu, Indah; Muckorobin, Moch. Ilham (Indonesian Journal of Educational Counseling, 2023)
The purpose of this literature study is to help individuals to be more confident by looking for the abilities that exist within them. This article reviews four main points of writing, which cover (1) Basic philosophy, (2) Human nature, (3) Personality structure, (4) Ego defense mechanism, and (5) Personal development psychoanalytic counseling. The method used for this article is a literature study. Psychoanalysis is a useful theory for the analysis of human psychology. Sigmund Shlomo Freud developed this theory due to a bad incident between him and his father. This theory has three structures, namely the id, ego, and superego, in which these three elements continuously interact and result in encouragement within oneself, giving birth to healthy and unhealthy behaviors.